Biological denitrification process based on the Fe(0)–carbon micro-electrolysis for simultaneous ammonia and nitrate removal from low organic carbon water under a microaerobic condition. (November 2016) - Deng, Shihai; Li, Desheng; Yang, Xue; Xing, Wei; Li, Jinlong; Zhang, Qi
Highlights: Denitrification was enhanced by micro-electrolysis-based electron donor production. Efficient simultaneous nitrification and autotrophic denitrification was obtained. High nitrogen removal load was maintained for low organic carbon water treatment. HTS showed significantly increases in genera Hydrogenophaga and Sphaerotilus . Dominant classes belonged to β -, α -, and γ - Proteobacteria, as well as Nitrospira . Abstract: A combined process between micro-electrolysis and biological denitrification (MEBD) using iron scraps and an activated carbon-based micro-electrolysis carrier was developed for nitrogen removal under a microaerobic condition. The process provided NH4 + –N and total nitrogen (TN) removal efficiencies of 92.6% and 95.3%, respectively, and TN removal rate of 0.373 ± 0.11 kg N/(m 3 d) at corresponding DO of 1.0 ± 0.1 mg/L and HRT of 3 h, and the optimal pH of 7.6–8.4. High-throughput sequencing analysis verified that dominant classes belonged to β -, α -, and γ - Proteobacteria, and Nitrospira . The dominant genera Hydrogenophaga and Sphaerotilus significantly increased during the operation, covering 13.2% and 6.1% in biofilms attached to the carrier in the middle of the reactor, respectively. Autotrophic denitrification contributed to >80% of the TN removal. The developed MEBD achieved efficient simultaneous nitrification and autotrophic denitrification, presenting significant potential for application in practical low organic carbon water treatment.